Effect of sulfate reduction activity on biological treatment of hexavalent chromium [Cr(VI)] contaminated electroplating wastewater under sulfate-rich condition - Chang, In Seop; Kim, Byung Hong (PERGAMON-ELSEVIER SCIENCE LTD, 2007)
Electroplating wastewater (EW) containing heavy metals was treated by a two-stage packed-bed reactor system. The EW was highly contaminated with hexavalent chromium and other heavy metals as well as sulfate because sulfuric acid had been mainly used to polish the surface of metals to be electroplated. This acidic EW was effectively neutralized in an alkaline reactor where limestone bad been packed. The neutralized wastewater together with organic wastewater from a starch-processing factory (SPW) was fed to a bioreactor packed with waste biomass. The SPW was used to supplement the electron donor in the sulfidogenic bioreactor. During the whole operation, we investigated the stoichiometry of electron to see what could be a major factor to remove Cr in the wastewater. The removal rates of sulfate and Cr(VI) were dependent on the consumption rate of organic materials in the wastewater. The stoichiometric studies also showed that about 63% of electrons from oxidation of organic materials were used to reduce sulfate. When the electrons of sulfide oxidation to elemental sulfur was at least 1.3 times higher than that of Cr(VI) reduction to Cr(111), Cr(VI) was completely removed. This result suggests that Cr(VI) reduction can be expected to take place under sulfate-rich anaerobic conditions, and sulfide produced by sulfate reducing bacteria could be used to immobilize soluble chromium through Cr(VI) reduction. (C) 2007 Elsevier Ltd. All rights reserved.
Keywords: REDUCING BACTERIA; DESULFOVIBRIO-DESULFURICANS; REMOVAL; WASTEWATERS; BIOREACTOR; TOXICITY; STRAIN; METAL